A GIS-based analysis of hillfort location and morphology - Murray, J (2016)
Moving away from the highly regionalised and constrained purely humanistic and empirical studies of hillfort location and morphology, this study is a multi-regional GIS-based analysis of the form and siting of several groups of hillforts across Britain. Hillforts in Dartmoor, Aberdeenshire, The Gower and Warminster are assessed, four regions that are topographically diverse. The highly varied topography of these regions also tests the GIS-basis of this study, another important intrinsic aspect of this novel research. GIS-based analysis has never before been applied to a study of hillfort location and morphology to this degree and, as with any innovative methodology its worth has to be tested and assessed. The thesis demonstrates that GIS-based analysis, when combined with field visits, provides a fundamental insight into the possible influences of hillfort location and morphology, which fieldwork alone will never be able to do. The GIS-based analysis developed here focuses largely upon examining degrees of movement and visibility. Unlike other GIS-based analyses of movement and visibility this integrates the two to examine visual pathways across landscapes to further investigate the visual qualities of hillforts within the various test areas. The study demonstrates that GIS-based analysis when combined with fieldwork can be affectively applied to qualitative based questions surrounding hillfort location and morphology. The overall results of this analysis had some relatively predictable results whilst there were some very surprising cases. A large number of entrances were placed within the most accessible area, however in the case of Battlesbury there was evidence for the complete disregard to accessibility within the orientation of its northwestern entrance. There were also numerous examples of the placement of a site's most prominent morphological components in correlation with the blind pathways. In these cases sites were orientated to encourage an element of surprise upon the approaching travellers.